Anterior Vertebral Body Tethering Compared with Posterior Spinal Fusion for Major Thoracic Curves: A Retrospective Comparison by the Harms Study Group. (21st December 2022) - Newton, Peter O.; Parent, Stefan; Miyanji, Firoz; Alanay, Ahmet; Lonner, Baron S.; Neal, Kevin M.; Hoernschemeyer, Daniel G.; Yaszay, Burt; Blakemore, Laurel C.; Shah, Suken A.; Bastrom, Tracey P.
Abstract : Background: Anterior vertebral body tethering (AVBT) is an alternative to posterior spinal fusion (PSF) for the surgical treatment of scoliosis. The present study utilized a large, multicenter database and propensity matching to compare outcomes of AVBT to PSF in patients with idiopathic scoliosis. Methods: Patients with thoracic idiopathic scoliosis who underwent AVBT with a minimum 2-year follow-up retrospectively underwent 2 methods of propensity-guided matching to PSF patients from an idiopathic scoliosis registry. Radiographic, clinical, and Scoliosis Research Society 22-Item Questionnaire (SRS-22) data were compared preoperatively and at the ≥2-year follow-up. Results: A total of 237 AVBT patients were matched with 237 PSF patients. In the AVBT group, the mean age was 12.1 ± 1.6 years, the mean follow-up was 2.2 ± 0.5 years, 84% of patients were female, and 79% of patients had a Risser sign of 0 or 1, compared with 13.4 ± 1.4 years, 2.3 ± 0.5 years, 84% female, and 43% Risser 0 or 1 in the PSF group. The AVBT group was younger (p < 0.001), had a smaller mean thoracic curve preoperatively (48 ± 9°; range, 30° to 74°; compared with 53 ± 8°; range, 40° to 78° in the PSF group; p < 0.001), and had less initial correction (41% ± 16% correction to 28° ± 9° compared with 70% ± 11% correction to 16° ± 6° in the PSF group; p < 0.001). Thoracic deformity at the time of the latest follow-up was 27° ± 12° (range, 1° to 61°) for AVBT compared with 20° ± 7° (range, 3° to 42°) for PSF (p < 0.001). A total of 76% of AVBT patients had a thoracic curve of <35° at the latest follow-up compared with 97.4% of PSF patients (p < 0.001). A residual curve of >50° was present in 7 AVBT patients (3%), 3 of whom underwent subsequent PSF, and in 0 PSF patients (0%). Forty-six subsequent procedures were performed in 38 AVBT patients (16%), including 17 conversions to PSF and 16 revisions for excessive correction, compared with 4 revision procedures in 3 PSF patients (1.3%; p < 0.01). AVBT patients had lower median preoperative SRS-22 mental-health component scores (p < 0.01) and less improvement in the pain and self-image scores between preoperatively and the ≥2-year follow-up (p < 0.05). In the more strictly matched analysis (n = 108 each), 10% of patients in the AVBT group and 2% of patients in the PSF group required a subsequent surgical procedure. Conclusions: At a mean follow-up of 2.2 years, 76% of thoracic idiopathic scoliosis patients who underwent AVBT had a residual curve of <35° compared with 97.4% of patients who underwent PSF. A total of 16% of cases in the AVBT group required a subsequent surgical procedure compared with 1.3% in the PSF group. An additional 4 cases (1.3%) in the AVBT group had a residual curve of >50° that may require revision or conversion to PSF. Level of Evidence: Therapeutic Level III . See Instructions for Authors for a complete description of levels of evidence.